The WASh Trial: water-assisted sigmoidoscopy in the English Bowel Scope Screening Programme: study protocol for a randomized multicenter trial - Beintaris, Iosif; Esmaily, Shiran; Saunders, Brian P.; Rees, Colin J.; Von Wagner, Christian; Tsiamoulos, Zacharias; Hoare, Zoe; Evans, Rachel; Yeo, Seow Tien; Edwards, R. T.; Larkin, Tony; Veitch, Andrew; Chilton, Andrew; Bramble, Michael G.; Deane, Jill; Rutter, Matthew D. (Endoscopy International Open, 2019)
Background and study aims The English National Bowel Scope Screening Programme (BSSP) invites 55-year-olds for a one-off, unsedated flexible sigmoidoscopy (FSIG). Data from BSSP participant-reported experience studies shows 1 in 3 participants report moderate or severe discomfort. Water-assisted colonoscopy (WAS) may improve participants’ comfort. The primary objective of this study is to ascertain if post-procedural participant-assessed pain is reduced in WAS compared with carbon dioxide (CO2) insufflation, in invitees undergoing FSIG in BSSP.Patients and methods This is a multicenter, prospective, randomized, two-arm, single-blinded trial designed to evaluate the performance of WAS versus CO2 insufflation in BSSP. Participants will be randomized to either CO2 or WAS and will be asked to rate pain post-procedure. Key procedure-related data will be analyzed, including adenoma detection rates (ADR) and degree of sigmoid looping. A cost-effectiveness analysis of WAS versus CO2 and a discrete choice experiment exploring preferences of participants for attributes of sigmoidoscopy will also be performed.Discussion This is the first trial in the United Kingdom (UK) to investigate the effects of WAS in a screening setting. If the trial shows WAS either reduces pain or increases ADR, this may result in a practice change to implement WAS in screening and non-screening endoscopic practice directly impacting on 256,000 people a year who will undergo BSSP FSIG by 2020.Trial funding came from National Institute for Health Research (NIHR) Research for Patient Benefit (RfPB) supported by the NIHR Clinical Research Network. The trial is actively recruiting. ID: 35866 ISRCTN: 81466870